A naphthalene-based fluorescent probe with a large Stokes shift for mitochondrial pH imaging. Issue 20 (21st September 2018) - Lin, Bo; Fan, Li; Ge, Jinyin; Zhang, Wenjia; Zhang, Caihong; Dong, Chuan; Shuang, Shaomin
Abstract : A naphthalene-based fluorescent pH probe with a p K a of 8.8 for imaging mitochondrial pH changes in live cells. Abstract : A mitochondrial-targeted pH fluorescent probe 4-(2-(6-hydroxynaphthalen-2-yl)vinyl)-1-methylpyridin-1-ium was facilely synthesized via the carbon–carbon double bond bridging of 6-hydroxy-2-naphthaldehyde and 1, 4-dimethylpyridinium iodide salt. The probe exhibited remarkable pH-dependent behavior in the linear range of 7.60–10.00, with a p K a value of 8.85 ± 0.04 near mitochondrial pH. A significantly large Stokes shift of 196 nm was obtained, which reduces the interference of excitation light. Application of the probe in live HepG2 cells indicated that the probe had excellent mitochondrial targeting ability and was successfully used to visualize mitochondrial pH fluctuations in live cells.